Educação ambiental na comunidade quilombola de Mata Cavalo : diálogos da arte, cultura e natureza - Soares, Cristiane Carolina de Almeida (2018)
The paths that led to this dissertation have a deep relationship with the resumption of the artistic and cultural manifestations which are fundamental in the popular education process, which strengthens knowledge and the fight for the right to occupy and remain in the ancestral territory of the Maroon community of Mata Cavalo, which resists on the margins of power and produces its knowledge to the consecration of its own inequality. This place represents a territory rich in knowledge, doings and conflicts as well. Its history is marked by a myriad of prejudice which resulted in a policy of social exclusion. Our aim was to make a social mapping with emphasis on the culture of the Maroon Community Mata Cavalo, through dialogues of arts-based environmental education. When taking methodological paths, we were inspired by the Social Map methodology, which sought the cultural aspects as resistance tactics to strengthen this group to face the conflicts and defend the territory. Mapping the dialogical dimensions which intertwine art, culture and nature, we sought educational possibilities of the Maroon valorization. We gathered perceptions and sought selfnarratives that could translate the collective fights, dreams and desires of this community. Dialogues of arts-based environmental education were set up, in order to give visibility to this Maroon community, in its multiplicities. When visualizing the Maroon cultural manifestations, we were able to gather and appreciate the four dimensions mapped in the researcher’s pathway: historical landmarks, artistic expressions, typical foods and festivals, wherever arts-based environmental education promotes its dialogues. Socio-poetic inspiration offered us the beauty of being in communion with a research group that senses environmental education, through dialogues and partnerships, pointing to the gradual construction of a shared and sensitive wisdom between the researchers and the Maroon community. In all the ethnographic aspects, we found reference to resistance empowering people in this Maroon community, who represented an important role during the design of this research: in the interviews, in the construction of maps and in all the dialogical moments. In the results of this investigative journey, participatory mapping promoted discussions and reflections on the link among art, culture and nature, and the desire for visibility which pulsates in the heart of this people. On many occasions we could see that the hope of this community echoes in the toils, where environmental education, art and culture play an important articulating role, in educational or not educational spaces, which became territories of legitimate fight for the preservation of habits of the Maroon ancestors.